Around the Oven and the Table. Practices of Living of Textile Industry Workers from Łódź - Karpińska, Grażyna Ewa (In the Kitchen. Cultural Sketches on Space, 2019)
The lack of a room in the architectural block of a house that would serve the function of a kitchen – a feature of unicameral housing built for workers before World War II. Only the collected and spaced out equipment and objects established the landscape of the kitchen (people and objects), in which the residents cooperated and which “evoked” certain interactive responses from the human side. In the article, from the perspective of residential habitation, I look at objects and their structuring within a fragment of the space of a flat called a kitchen. I rely on the material collected during many years of research on the interior of housing for workers’ families, which I conducted with students of ethnology at the turn of the seventies and eighties of the twentieth century in Lodz, among residents of tenement houses and family homes built by manufacturers for “their” workers. Among the collected accounts, I choose the ones that the workers who deal with the families lived in the same apartments before and after the war, because I want to look at living as a practice that connects with generational staying in a certain space and passing patterns of her domestication.